Set-to-set performance variation in tennis grand slams: play with consistency and risks - Cui, Y.; Liu, H.; Gómez, M. Á.; Liu, H.; Gonçalves, B. (Journal of Human Kinetics, 2020)
The study analysed the set-to-set variation in performance using match statistics of 146 completed main-draw matches in Australian Open and US Open 2016-2017 men`s singles. Comparisons of technical-tactical and physical performance variables were done between different sets; and the within-match coefficients of variation (CV) of these variables were contrasted between match winning and losing players. All comparisons were realized via standardized (Cohen`s d) mean differences and uncertainty in the true differences was assessed using non-clinical magnitude-based inferences. Results showed that there was possibly to very likely decreases in the serve, net and running related variables (mean difference, ±90%CL: -0.16, ±0.14 to -0.45, ±0.24, small) and an increase in the return and winner related variables (0.17, ±0.24 to 0.24, ±0.14, small) in the last sets when compared to the initial sets, indicating the influence of match fatigue and the player`s choice of match tactics and pacing strategy. Besides, winning players were revealed to have lower CV values in most of performance variables (-0.16, ±0.24 to -0.82, ±0.23, small to moderate) except for the second serve, winner, and physical performance variables (0.25, ±0.26 to 1.6, ±0.25, small to large), indicating that they would sacrifice the consistency to gain more aggressiveness and to dominate the match.